Highly shape- and regio-selective peroxy–trifluoromethylation of styrene by metal–organic framework Cu3(BTC)2. Issue 24 (6th November 2017) - Qi, Bo; Zhang, Tiexin; Li, Mochen; He, Cheng; Duan, Chunying
Abstract : The peroxy and trifluoromethyl groups play important roles in pharmacy, but it is challenging to introduce both of them selectively into the target molecules in a homogeneous catalytic system. Abstract : The peroxy and trifluoromethyl groups play important roles in pharmacy, but it is challenging to introduce both of them selectively into the target molecules in a homogeneous catalytic system. In the presence of the easily available metal–organic framework Cu3 (BTC )2 (also well known as HKUST-1), novel peroxy–trifluoromethylation of styrenes was achieved in a heterogeneous mode. The rigid 3D framework of Cu3 (BTC )2 is necessary to maintain the structural integrity of the binuclear paddle-wheel Cu(ii ) catalytic center for the effective electrophilic activation of Togni's reagent and TBHP with a low loading amount of the catalyst and its easy re-use, and the bowl bottom-like confined environment around the copper node is vital for the discrimination of reaction sites with different steric demands. Compared with homogeneous copper salts, the heterogeneous Cu3 (BTC )2 showed superior catalytic activity and intrinsic shape- and regio-selectivity for this reaction. The peroxy moieties of the products could be easily converted to carbonyl or hydroxyl groups for further applications.